Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
(-1, 8)
Step-by-step explanation:
Make y the subject:
x + y = 7 ⟹ y = -x + 7
1. Substitute the value for y into 7x + y = 1 and solve for x:
7x + (-x + 7) = 1
7x - x + 7 = 1
6x + 7 = 1
6x + 7 - 7 = 1 - 7
6x = -6
6x ÷ 6 = -6 ÷ 6
x = -1
2. Substitute the given value of x into x + y = 7 and solve for y:
x + y = 7
-1 + y = 7
-1 + 1 + y = 7 + 1
y = 8
Therefore, the solution to this system of equations is: (-1, 8).
Learn more here:
brainly.com/question/2648990
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.